1999
DOI: 10.1136/bjo.83.9.1027
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for treatment outcome of suspected microbial keratitis

Abstract: Background-Primary treatment for suspected microbial keratitis is generally successful. Although risks such as contact lens use are well recognised as causative factors for microbial keratitis, little is known about the risk factors that influence treatment outcome. The present study evaluates the risk factors assessed at diagnosis as prognostic indicators of primary treatment failure. Methods-Patients were prospectively enrolled in the ofloxacin treatment trial and data concerning symptoms, treatments, past a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
45
5
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 13 publications
6
45
5
1
Order By: Relevance
“…In the present study, 61% of patients were on treatment with topical antimicrobials at presentation; although the overall isolation rate was 33%, the isolation rate was 27% for those on treatment and 42% for those not on treatment. This effect of pretreatment may account in part for the isolation rate being lower than that reported in previous studies (20,22). For example, Morlet et al (22) reported an isolation rate of 41.5% for a group of patients of whom only 22% were receiving topical antimicrobial medications, while McCleod et al (20), having excluded patients who had had prior treatment, obtained an isolation rate of 69.1% (56/81).…”
Section: Discussioncontrasting
confidence: 47%
“…In the present study, 61% of patients were on treatment with topical antimicrobials at presentation; although the overall isolation rate was 33%, the isolation rate was 27% for those on treatment and 42% for those not on treatment. This effect of pretreatment may account in part for the isolation rate being lower than that reported in previous studies (20,22). For example, Morlet et al (22) reported an isolation rate of 41.5% for a group of patients of whom only 22% were receiving topical antimicrobial medications, while McCleod et al (20), having excluded patients who had had prior treatment, obtained an isolation rate of 69.1% (56/81).…”
Section: Discussioncontrasting
confidence: 47%
“…At least one of these predisposing factors was detected in 35% of the patients in this study. WCL, associated ocular disease, and corneal trauma were seen as the main local risk factors [9][10][11][12]. Most notably, WCL has frequently been associated with severe forms of microbial keratitis [13].…”
Section: Discussionmentioning
confidence: 99%
“…In our hospital, the most common indications for enucleation and evisceration in this age group were nonresolving severe keratitis (30 patients, 64%) and corneal perforation (17 patients 36%). The variables found to be associated with adverse outcomes in cases of microbial keratitis in the past include severe infection [12][13][14][15], advanced patient age [13,16,17], poor visual acuity at presentation [13,15,17], associated herpetic keratitis [14,18], ocular surface disease [12], associated systemic disease [12], prior treatment with steroids [19], and a delay in seeking treatment [20]. Failure to use fortified antibiotics has also been found to be associated with poor prognosis in cases with microbial keratitis [20].…”
Section: Discussionmentioning
confidence: 99%